Adsorption equilibrium and kinetics of methylene blue on rice husk ash straw Composites. Issue 3 (April 2021) - Liguang, Xiao; Ke, Sun
Abstract: In this paper, corn straw in Jilin area was used as the base material, and the corn straw was modified by the alkaline solution system formed by urea trisodium phosphate sodium tetraborate, then the residue of rice husk burning in power plant was added. The rice husk ash / straw composite material was made by spin coating evaporation process, and the adsorption performance of methylene blue in wastewater was explored, and the linear regression analysis was carried out by Origin software The kinetic equation was obtained by regression fitting. The experimental results showed that: when the ratio of rice husk ash and straw was 1:2, the adsorption performance of methylene blue in wastewater was the highest, the adsorption rate was 96.3%, and the maximum adsorption capacity was 578.0mg/g; at the same time, it was found that the kinetic model was in line with the pseudo second order adsorption kinetic model, indicating that the adsorption process of methylene blue in wastewater by rice husk ash / straw composite was mainly chemical reaction.